THE RELATIONSHIP BETWEEN CERTAIN ANTHROPOMETRIC MEASUREMENTS AND THE SPEED AND FEASIBILITY OF PERFORMING THE OVERHEAD PASS SKILL AMONG JUNIOR VOLLEYBALL PLAYERS - Farqad Farhan Hameed; Riyadh Ali Muhsin (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Anthropometric characteristics play a crucial role in influencing skill performance in sports, particularly in technical disciplines like volleyball. Among junior athletes, understanding the impact of body dimensions on fundamental skills can guide talent identification and training strategies. Objectives. This study aimed to examine the relationship between selected anthropometric measurements (body height, weight, arm length, forearm length, hand length, trunk length, and shoulder circumference) and the speed and feasibility of performing the overhead pass skill among junior volleyball players. Methods. A descriptive-correlational approach was employed, involving 20 junior players from the Specialized School in Al-Chibayish District, Dhi Qar Governorate, during the 2023–2024 sports season. Anthropometric data were collected using standardized protocols, while the overhead pass skill was assessed through performance-based tests designed to measure accuracy and execution efficiency. Results. The findings revealed a statistically significant relationship between certain anthropometric variables—specifically arm length, forearm length, and shoulder circumference—and the accuracy and feasibility of performing the overhead pass. These variables were positively associated with improved skill execution. Conclusions. The results indicate that specific anthropometric characteristics can significantly enhance the performance of overhead passing in junior volleyball players. Early identification of these traits can support more effective talent selection and targeted training interventions. This study contributes to the field of youth sports science by emphasizing the relevance of body measurements in skill performance. It provides a practical framework for coaches and talent scouts to integrate anthropometric assessments into the selection and development process of junior volleyball players. The researchers recommend considering anthropometric measurements as essential indicators when selecting players at early age stages.